2022
DOI: 10.1007/s12144-022-03209-5
|View full text |Cite
|
Sign up to set email alerts
|

Validation and psychometric properties of the Italian Vaccination Attitudes Examination (VAX-I) scale

Abstract: Despite the massive volume of scientific evidence on the benefits of immunisation, vaccine hesitancy is still a global health threat and represents an obstacle to controlling the spread of viruses such as SARS-CoV-2 and its associated COVID-19. Thus, the present study aimed to adapt and validate an Italian version of the Vaccination Attitudes Examination (VAX) scale. The Italian version of the scale (VAX-I), along with validation measures (general health perceptions, perceived sensitivity to medicines, intenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Attitudes toward vaccination were evaluated using the Italian version of the Vaccination Attitudes Examination Scale (VAX-I scale; Martin and Petrie, 2017;Bruno et al, 2022). It consists of 12 items which can be divided into four subscales (mistrust of vaccine benefit, worries about unforeseen future effects, concerns about commercial profiteering, and preference for natural immunity), each indicated by three items.…”
Section: Measures Vaccination Attitudes Examination Scalementioning
confidence: 99%
“…Attitudes toward vaccination were evaluated using the Italian version of the Vaccination Attitudes Examination Scale (VAX-I scale; Martin and Petrie, 2017;Bruno et al, 2022). It consists of 12 items which can be divided into four subscales (mistrust of vaccine benefit, worries about unforeseen future effects, concerns about commercial profiteering, and preference for natural immunity), each indicated by three items.…”
Section: Measures Vaccination Attitudes Examination Scalementioning
confidence: 99%
“…The following themes emerged: (1) pregnancy is considered an independent risk factor for adverse outcomes in case of SARS-CoV-2 infection; (2) mistrust, anxiety and scepticism of COVID-19 vaccine safety and effectiveness are the main determinants of vaccine hesitancy in pregnant women [ 19 , 20 , 21 , 22 , 23 , 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…The following scales were consulted to build the questionnaire ( Supplementary Files ): Vaccination Attitudes Examination (VAX) scale [ 19 , 23 ], with good internal consistency, and the State Trait Anxiety Inventory (STAI) scale, an excellent scale with Cronbach’s α = 0.93 and good test/retest reliability with an intra-class correlation coefficient of 0.80 [ 24 , 25 ].…”
Section: Methodsmentioning
confidence: 99%
“…Results revealed that the Arabic version of the 5 C scale is a valid and reliable tool to assess the psychological antecedents of the COVID-19 vaccine among the Arab population. [7] examined the validation indicators of an Italian version of the Vaccination Attitudes Examination (VAX) scale; the results showed that the VAX-I scale appears to be a valid instrument to assess vaccine hesitancy in the Italian context. Finally, [16] tested the validation of the Multidimensional Covid-19 Vaccine Hesitancy Scale (CoVaH) in the Hungarian context, the CoVaH displayed excellent fit indices and internal consistencies and was found to have good validity in identifying Covid-19 vaccine hesitancy in the general population.…”
Section: Theoretical Backgroundmentioning
confidence: 99%